2006
DOI: 10.1002/qua.21016
|View full text |Cite
|
Sign up to set email alerts
|

Theory of chemical bonds in metalloenzymes III: Full geometry optimization and vibration analysis of ferredoxin‐type [2Fe–2S] cluster

Abstract: The nature of chemical bonds in a ferredoxin-type [2Fe-2S] cluster hasbeen investigated on the basis of natural orbitals and several bond indices developed in Parts I and II of this study. The broken-symmetry hybrid density functional theory (BS-HDFT) with spin projection approach has been applied to elucidate the natural orbitals and occupation numbers for a model compound [Fe 2 S 2 (SCH 3 ) 4 ] (1), which is used to calculate the indices. The molecular structure, vibration frequencies, electronic structures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 61 publications
4
35
0
Order By: Relevance
“…For instance, approximate spin projection corrections are up to , 0.1 Å for the Fe -Fe distance of [2Fe -2S] clusters for calculations at the BP86/BSIV [96] level and the B3LYP level using a double-z basis set [60]. However, there is no automated method for adding either projection correction into geometry optimisation, and the corrections are rather small.…”
Section: Further Improvementsmentioning
confidence: 99%
“…For instance, approximate spin projection corrections are up to , 0.1 Å for the Fe -Fe distance of [2Fe -2S] clusters for calculations at the BP86/BSIV [96] level and the B3LYP level using a double-z basis set [60]. However, there is no automated method for adding either projection correction into geometry optimisation, and the corrections are rather small.…”
Section: Further Improvementsmentioning
confidence: 99%
“…23 A large literature has developed on this and related broken-symmetry approaches. [24][25][26][27][28][29][30][31][32][33] Broken-symmetry solutions have also been studied in other contexts, and it has often been found that it is important to allow the orbitals to break symmetry in order to get a qualitatively correct description of the system. [33][34][35][36][37][38][39][40][41][42] The energies of the broken-symmetry states are often used without correcting for their spin character.…”
Section: Introductionmentioning
confidence: 99%
“…Computationally this implies severe limitations in terms of system size and coupling to molecular dynamics (MD). A well established compromise in terms of cost versus accuracy are spin-projection schemes (11, 12) that rely on an approximate purification of the spin state (13) by carrying out independent total energy calculations for several uncoupled spin configurations (14,15). Such approaches allow the calculation of the exchange coupling constant J directly and have been proven to perform particularly well for binuclear homovalent clusters in static calculations (16, 17).…”
mentioning
confidence: 99%